'Approved for use in uveitis': drug approval for an orphan disease. (July 2015) - Metzinger, Jamie Lynne; Foster, C Stephen
<x xml:space="preserve">Abstract</x> Introduction: Uveitis, a leading cause of preventable blindness around the world, is a critically underserved indication with regard to medications approved for use. Appropriate therapy routines for uveitis often involve a combination of corticosteroid and immunomodulating chemotherapies, dependent on patient presentation and diagnosis, clinical response and observed side effects, if any. Obtaining many of these medications can involve a lengthy appeals process after insurance denial, as all corticosteroid-sparing immunomodulatory therapies are utilized in an 'off-label' fashion. Areas covered: The purpose of this manuscript is to comprehensively review the current status of medications approved for use in uveitis: those that hold approval currently, and those that are undergoing clinical trials in the indication of uveitis. Additionally, points of consideration for clinical development – specifically with regard to clinically meaningful end points – are discussed. Expert opinion: Determination of clinically meaningful end points, which may entail revisiting the current clinical assessments used to determine efficacy, is crucial to future drug development with regard to uveitis. Approval in this indication may potentially expand access to pharmacologics for the treatment of this orphan disease.